ANALISIS PERFORMANSI TURBIN PROPELLER OPEN FLUME TIPE TC 60 KAPASITAS 100 W TERHADAP PERUBAHAN DEBIT - Wahyu K Sugandi; Dwi R Kendarto; Sophia Dwiratna; Arif Rahmanda (The University of Lampung, 2021)
The TC 60 open flume propeller turbine is an example of a pico-hydro-based fluid engine. The potential of the TC 60 open flume propeller turbine can be maximized by paying attention to the flow rate. This study aims to analyze the performance of the TC 60 open flume propeller turbine performance which is influenced by changes in discharge. The method used is descriptive analysis method. The turbine performance testing was carried out at the CV Cihanjuang Inti Teknik laboratory in Cimahi. Turbine testing begins by making 9 discharge ranges from 1.28 litre/sec until 4.85 litre/sec then testing each of these flows. Power testing is carried out using a lamp load of 10 to 100 watts. The results showed the effect of changes in discharge on the power generated by the turbine. The maximum power produced in this study is 74 watts at a discharge flow of 4.85 litre/sec with a load of 70 watts. The lowest discharge to be able to move the turbine is 1.28 litre/ sec. The results of the technical feasibility analysis on civil buildings in CV Cihanjuang Teknik show that the TC 60 open flume propeller turbine is feasible to use by considering the design of the discharge, head and channel shape of civil buildings. Keywords: discharge, picohydro, propeller turbine, performance